C. Henry Kempe: A 50 Year Legacy to the Field of Child Abuse and Neglect - Krugman, Richard D.; Korbin, Jill E.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
This volume is the first book in the new series, Child Maltreatment: Contemporary Issues in Research and Policy. This first volume focuses on the legacy of the work of C. Henry Kempe, M.D., the pediatrician widely credited with galvanizing public and private attention to abused and neglected children. 2012 marks 50 years after the appearance of the foundational article by C. Henry Kempe and his colleagues. (3z(BThe Battered- Child Syndrome.(3y (BThis volume capitalizes on this 50 years anniversary to stand back and assess the field from the perspective of Dr. Kempe's early contributions that are still being played out in research, practice and policy today. Dr Kempe produced many influential publications. The volume uses four key publications to solicit commentary and reflection on the field.s
Keywords: Social sciences; Public health; Pediatrics; Quality of Life; Social work; Quality of Life -- Research; Developmental psychology; Social Sciences; Quality of Life Research; Pediatrics; Child and School Psychology; Social Work; Public Health